Features of angiotensin II expression in the arcuate nucleus of the hypothalamus of experimental rats with arterial hypertension of various etiology - S. V. Tishсhenko (Patologìâ)
It is proved that the effctiveness of blood pressure regulation mainly depends on those neuromodulators and neurohormones that are formed in or enter the hypothalamus. The important role of the arcuate nucleus (ArC) both as the intrahypothalamic regulator of the functional activity of its nuclear structures, and the coordinator over the suprasegmental and segmental centers of blood pressure regulation is proved. There are data that blood pressure is dependent on the content of the pressor neurohormone angiotensin II in the ArC of hypothalamus. The aim of the study was to determine the specifi properties of angiotensin II content in the ArC of hypothalamus in the rats of Wistar and SHR lines with etiologically diffrent arterial hypertension: endocrine-salt and essential. Materials and methods. The study was carried out on 24 mature male rats 250–270 g weight at the age of 13–14 months, which were divided into three experimental groups each consisting of 8 animals. First group of the Wistar rats with normal BP parameters (Ps/Pd = 110/75 ± 5 mm) was a control one. The second was the group of Wistar rats with the endocrine-salt model of arterial hypertension (Ps/Pd 145/110 ± 10 mm). The third group was presented by the SHR rats with spontaneous arterial hypertension (Ps/Pd = 150/110 ± 10 mm). An immunohistochemical method was used to study the content of angiotensin II in the ArC, which was followed by digital processing of the data by Image J and EXCEL-7.0. Results. Reduction in the content and concentration of angiotensin II is observed in the rats with arterial hypertension independently of its etiology and pathogenesis. Peculiarities of angiotensin II content in ArC of hypothalamus are dependent from the etiology and pathogenesis of arterial hypertension. In essential hypertension (SHR) lower levels of angiotensin II expression in the ArC structure of the hypothalamus are observed than in secondary endocrine associated arterial hypertension.